Curriculum development through understanding the student nurse experience of suicide intervention education – A phenomenographic study. Issue 6 (November 2015) - Heyman, Inga; Webster, Brian J.; Tee, Stephen
Abstract: Suicide remains a global public health issue and a major governmental concern. The World Health Organisation argues for continued investment in education for front-line professionals, with a particular focus on nurses, to address the rising suicide levels. Considering this rate, it could be argued that suicide has impacted on the lives of many, including the student nurse population. Understanding the psychological impact, and influence on learning, whilst developing suicide intervention knowledge is crucial. However, little is known of the student experience in this complex and challenging area of skills development. This phenomenographic study examines the experiences of second year Bachelor of Nursing (mental health) students who participated in the Applied Suicide Intervention Skills Training (ASIST). Experiences were illuminated through two focus groups, Experiences were distilled and categorised through hierarchically relationships to construct a group experiential field to illustrate understandings of the impact this approach has on learning Students found ASIST to be emotionally challenging yet an extremely positive experience through bonding, peer learning, and class cohesion. The supportive workshop facilitation was essential allowing for full immersion into role simulation thus developing student confidence. Appropriate pedagogy and student support must be considered whilst developing suicide intervention in the pre -registration curricula. Highlights: Suicide a global issue with governmental strategies to improve interventions. Intervention education is applicable to all undergraduate nurse education fields. Blending theory and role play supports effective bridging of theory/practice gap. Student experience must be considered in curriculum development.